An Interventional Approach to Enhance the Attitude and Participation of School Going Children towards Environmental Awareness in Prayagraj - Mary, Susheela; Thomas, Tarence; Hilda D’Souza, Metilda; P. Jose, Jessy (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
The present study attempts to survey the level of attitude and participation towards environmental awareness among School going children of Prayagraj District, of Uttar Pradesh. The sample consisted of 300 students which includes 150 Boys and Girls from Rural and Urban areas and 150 Boys and Girls from Rural and Urban area. The Descriptive Survey and random sampling Method were procured for the present study. Environmental attitude and participation scale were developed and standardized. The data was statistically analysed by using pre-test/t’-test and Taj Environmental Attitude Scale (TEAS). The attitude and participation towards Environmental awareness among school going children was found no difference (not significant) also in case of Urban and Rural students the attitude and Participation towards environmental awareness was not significant.
Keywords: Attitude; Environmental awareness; Participation; Secondary School